Current Architectural Problems of Samarkand Ancient Center Centers - H. H. Juraev; S. M. Suvankulov (Researchparks Publishing, 2022)
This scientific article is about the architectural problems of Samarkand’s ancient mahalla centers, critically examines some of the existing mahalla centers, and offers suggestions based on the principles of tradition